Ancillary findings on high resolution CT chest associated with typical features of COVID-19 pneumonia (Observational descriptive study at a tertiary care hospital) - Zafar, Saerah Iffat; Halim, Aliya; Nasir, Hina; Palwa, Abdur Rahim; Zafar, Nadeem; Burney, Shamaila (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of ancillary pulmonary signs and their relation to the severity of disease seen on high-resolution computed tomography of chest in patients of coronavirus disease-2019 pneumonia. Methods: The observational descriptive study was conducted at the Armed Forces Institute of Radiology and Imaging, Rawalpindi, Pakistan, from March to July 2020, and comprised all coronavirus disease-2019 patients who were found positive on reverse transcription-polymerase chain reaction-and were referred to have high-resolution computed tomography of chest. Ancillary pulmonary findings in addition to typical features of coronavirus disease-2019 pneumonia were recorded. These included vacuole sign, halo sign, reverse halo sign, subpleural white line, subpleural translucent line, microvascular dilatation, fibrotic streaks and bronchiectasis. Relative frequency of these signs were determined for mild versus and severe disease, as determined by the computed tomography severity score. Data was analysed using SPSS 26. Results: Of the 1645 patients, 1286(78.2%) were males and 359(21.8%) were females. The overall mean age was 47.5 15.7 years (range: 1-92). High-resolution computed tomography was normal in 418(25.4%) patients, typical findings for coronavirus disease-2019 were seen in 1110(67.5%), indeterminate in 113(16.9%) and atypical in 4(0.2%). Vacuole sign, subpleural white line, subpleural translucent sign, microvascular dilatation and fibrotic streaks were more commonly seen in severe disease (p<0.001), while discrete pulmonary nodule was identified more in the milder form (p<0.05). Halo and reverse halo signs as well as bronchiectatic changes demonstrated no significant propensity to the degree of disease severity (p>0.05). Conclusion: Coronavirus disease-2019 pneumonia demonstrated various ancillary pulmonary features on high-resolution computed tomography of the chest. Key Words: Ancillary, COVID, Pneumonia.